MODERN DIAGNOSTIC ALGORITHM OF ATOPY IN INFANTS - T.V. Turti; M.A. Snovskaya; O.V. Kozhevnikova (Union of pediatricians of Russia, 2011)
Difficulties in the timely effective prevention of the atopic process development are related to the lack of unified well-founded programs of primary and secondary prevention of allergy. The paper presents results of studies demonstrating the important role of food antigens in the early formation of the atopic status of the child. A modern algorithm for clinical and immunological diagnosis of atopy, identifying cause-significant allergens in infants has been worked out. Key words: infants, children of the first year of life, atopy, allergy, prevention, food antigens, IgE. (Pediatric pharmacology. - 2011; 8 (6): 68-73).